2020
DOI: 10.3390/cells9061425
|View full text |Cite
|
Sign up to set email alerts
|

Megalencephalic Leukoencephalopathy with Subcortical Cysts Disease-Linked MLC1 Protein Favors Gap-Junction Intercellular Communication by Regulating Connexin 43 Trafficking in Astrocytes

Abstract: Astrocytes, the most numerous cells of the central nervous system, exert critical functions for brain homeostasis. To this purpose, astrocytes generate a highly interconnected intercellular network allowing rapid exchange of ions and metabolites through gap junctions, adjoined channels composed of hexamers of connexin (Cx) proteins, mainly Cx43. Functional alterations of Cxs and gap junctions have been observed in several neuroinflammatory/neurodegenerative diseases. In the rare leukodystrophy megalencephalic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…The physiological function of MLC1 remains unknow. Previous work done in cell culture in Mlc1null mice suggest that MLC1 may be involved in astrocyte ion and volume regulation through its interaction with different chloride, potassium and cation channels, or with gap junction-forming connexin-43 [30][31][32][33][34][35] . Anatomically, immunogold-electron microscopic images in postmortem human tissue showed that MLC1 localized to the junctions connecting overlapping perivascular astrocytic endfeet 36 .…”
Section: Introductionmentioning
confidence: 98%
“…The physiological function of MLC1 remains unknow. Previous work done in cell culture in Mlc1null mice suggest that MLC1 may be involved in astrocyte ion and volume regulation through its interaction with different chloride, potassium and cation channels, or with gap junction-forming connexin-43 [30][31][32][33][34][35] . Anatomically, immunogold-electron microscopic images in postmortem human tissue showed that MLC1 localized to the junctions connecting overlapping perivascular astrocytic endfeet 36 .…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, the Na + /K + -ATPase pump has been identified as a MLC1-interacting protein, whereas the overexpression of MLC1 was observed to reduce its activity ( 11 ). Finally, Cx43 has been identified as a GlialCAM interacting protein ( 12 ) and MLC1 might influence Cx43 stability at gap junctions in astrocytoma cells ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…In ovarian cancer cells Axl signaling leads to reduced Erk1/2 phosphorylation and this correlates with a more epithelial-like cell state due to higher activities of the phosphatase DUSP4 [ 41 ]. MLC1 in astrocytes has also been reported to inhibit Erk1/2 signaling via connexins involved in direct cell-cell communication [ 42 ]. In addition, we have shown that the metastasis suppressor Ndrg1 is hyperphosphorylated in GSCs expressing MLC1 shRNAs, revealing that multiple pathways downstream of Mlc1 likely promote GBM cell polarity and invasion.…”
Section: Discussionmentioning
confidence: 99%